A Review Paper on Challenges in IoT Security (International Journal of Food and Nutritional Sciences, 2022)
The Internet of Things allows wearable devices, home appliances, and software to share and send data via the Internet (IoT). Maintaining information security on shared data is a crucial issue that must not be ignored, given the huge amount of private information included within. We begin with a fundamental review of IoT information security in this essay, and then go on to the information security problems that IoT will encounter. A future in which physical things are seamlessly connected to the information network and may become active players in corporate operations. The key characteristics that distinguish IoT security problems from conventional security issues are the diverse and large-scale devices and networks. IoT security is made considerably more challenging by these two characteristics, heterogeneity and complexity. The current problems and research possibilities in IoT security were discussed in this article. Finally, we'll talk about study topics that may lead to future work on solutions to the Internet of Things' security issues.